Adopting English-Taught Degree Programs - Bradford, Annette (International Higher Education, 2012)
The number of English-taught degree programs in non-English speaking countries is rapidly increasing. However successful implementation of these programs is not easy. Linguistic, cultural and structural challenges must be overcome.